Langkah Cerdas Membangun Marketplace UMKM Ayam Takapik Di Kota Padang Menggunakan Aplikasi Blogger - Divana Yuliant; Ghinaa Safitri; Julia Anggraini; Sularno; Nova Dilastri (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
This article discusses strategic steps in building a marketplace for Micro, Small, and Medium Enterprises (MSMEs) Ayam Takapik in Padang by utilizing the Blogger platform. This research aims to provide effective solutions for MSME actors to enhance their product visibility and accessibility in the digital era. The method used is qualitative analysis through observations and interviews with business owners and Blogger platform users. The results indicate that using Blogger as a marketing tool can improve interactions between entrepreneurs and consumers, expand market reach, and facilitate product promotion. The article concludes that with the right approach, Ayam Takapik MSMEs can leverage digital technology for sustainable growth. Recommendations for further implementation and the development of a more integrated marketplace system are also presented.